2019
DOI: 10.1042/bsr20190817
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ropivacaine on peripheral neuropathy in streptozocin diabetes-induced rats through TRPV1-CGRP pathway

Abstract: Objective To determine the effect of ropivacaine on peripheral neuropathy in diabetic rats and its possible mechanism.Methods Forty-eight Sprague–Dawley rats were randomly divided into six groups: nondiabetic control group, nondiabetic group A (0.25% ropivacaine), nondiabetic group B (0.75% ropivacaine), diabetic control group (diabetic peripheral neuropathy (DPN) +artificial cerebrospinal fluid), diabetic group A (DPN+0.25% ropivacaine), and diabetic group B (DPN + 0.75% ropivacaine), with eight rats in each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…It has also been demonstrated that expression of these markers were also reduced in peripheral nerves [122]. In addition, it has been shown that ropivacaine, which is a commonly used anesthetic in the treatment of peripheral neuropathy, has a protective effect against the development of diabetic peripheral neuropathy by regulating TRPV1 receptor mediated CGRP release [122]. In agreement with this study, another report has demonstrated that TRPV1 receptor antagonists such as capsazepine prevent hydrogen sulfide-induced hyperalgesia in diabetic rats [123].…”
Section: Role Of Trpv1 Receptor Insr and Insulin In The Development supporting
confidence: 62%
See 1 more Smart Citation
“…It has also been demonstrated that expression of these markers were also reduced in peripheral nerves [122]. In addition, it has been shown that ropivacaine, which is a commonly used anesthetic in the treatment of peripheral neuropathy, has a protective effect against the development of diabetic peripheral neuropathy by regulating TRPV1 receptor mediated CGRP release [122]. In agreement with this study, another report has demonstrated that TRPV1 receptor antagonists such as capsazepine prevent hydrogen sulfide-induced hyperalgesia in diabetic rats [123].…”
Section: Role Of Trpv1 Receptor Insr and Insulin In The Development supporting
confidence: 62%
“…Recent work using immunohistochemistry and western blot analysis has revealed that expression of TRPV1 receptor and CGRP decreased in spinal cord dorsal horn of in rats with streptozotocin (STZ) diabetes. It has also been demonstrated that expression of these markers were also reduced in peripheral nerves [122]. In addition, it has been shown that ropivacaine, which is a commonly used anesthetic in the treatment of peripheral neuropathy, has a protective effect against the development of diabetic peripheral neuropathy by regulating TRPV1 receptor mediated CGRP release [122].…”
Section: Role Of Trpv1 Receptor Insr and Insulin In The Development mentioning
confidence: 99%
“…It reversibly inhibits the nociceptive influx of sodium ions in nerve fibres by blocking propagation of action potentials. It also reduces the activity of the TRPV1 channel 5 . Thus, it may have a role in controlling neuropathic pain.…”
Section: Patient No 1 2 3 4 5 6 7 8 9 10mentioning
confidence: 99%
“…It also reduces the activity of the TRPV1 channel. 5 Thus, it may have a role in controlling neuropathic pain. Topical ropivacaine is known to be well tolerated.…”
Section: Efficacy Of Topical Ropivacaine In Children and Young Adultsmentioning
confidence: 99%
See 1 more Smart Citation